IMPACT OF THE USE OF SMART TRANSPORT SYSTEMS ON ECONOMIC GROWTH RATES IN UZBEKISTAN (American Journal of Interdisciplinary Research and Development, 2022)
This paper examines the relationship between the introduction of intelligent transportation systems and increased economic growth. The focus is on the following aspects: the concept of intelligent transport systems, their application areas and the consequences of their use.